An Ethnographic Review of Saubhagya Shah’s A Project of Memoreality (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
This review paper investigates a critical ethnographic method and its implication on the research conducted in a rural village in Nepal by Saubhagya Shah, a renowned anthropologist. The book, entitled A Project of Memoreality: Transactional Development and Local Activism, was published in 2018, nine years after the author’s demise in 2009 due to a massive heart attack. The author chose a rural village called Viman located in the mid-central part of Nepal as his field site to conduct an ethnographic study. The village was linguistically diverse, which challenged the author as he conducted ethnographic research in this community. Regardless of the economic disparities and cultural diversities, Saubhagya decided to explore women’s issues, including the activism of women involved in social development and in liberation from patriarchal hegemony. This book employs an ethnographic investigation to explore how women in a rural village of Nepal (Viman) are involved in the social activism and development process, as well as how national and international agencies helped them promote their activism through forming an organization. However, this review critically examines how such ethnographic research conceptualizes theoretical framework, methodological implementation, reflexivity, and objectivity from the fieldwork to the data analysis carried out through the observation the author makes. To help the reader better understand the methodological ideas reasonably, I divided this piece of writing into several units in terms of the author’s excursion from an ordinary person into becoming a well-known anthropologist contributing to the lacuna of Nepali academic knowledge in ethnographic studies. This review has discussed the ideas used for and the activities performed in this project based on ethnographic methods after a brief introduction. Methods implemented in the research and the challenges the author encountered during his fieldwork are in the third section, followed by a description of the theoretical framework the author employed in section four and the notion of the reflectivity and the objectivity manifested on this project in section five. Towards the end, the author’s positionality and a concluding remark have been critically examined in units six and seven, respectively.